Retinal Dysplasia Mimicking Retinoblastoma - Ravikumar HN; Vani Ravikumar; Santosh KV; Annie Joji (Online Journal of Health & Allied Sciences, 2012)
Retinal dysplasia represents a congenital disorder characterized by abnormal proliferation of retinal tissue causing leukocoria. We present a case of an infant with bilateral leukocoria, clinically diagnosed as retinoblastoma, followed by enucleation of the left eye. Microscopy however, demonstrated retinal dysplasia consisting of a disorderly proliferation of retinal tissue with formation of rosettes, mimicking retinoblastoma. Microscopic features that aid in differentiating this lesion from retinoblastoma are discussed.